Asymmetrical and symmetrical naphthalene monoimide fused perylene diimide acceptors for organic solar cells. (18th June 2022) - Yan, Bangzheng; Wang, Xin; Hu, Cetao; Wu, Di; Xia, Jianlong
Abstract: Perylene diimide (PDI) and its derivatives have received intensive research attention due to their promising applications in organic electronics, such as organic solar cells (OSCs) and organic field-effect transistors (OFETs). Fusing PDI with other arene imide is a robust strategy for the construction of high performance n-type organic semiconductors. In this work, we report two PDI derivatives (asymmetrical FPN and symmetrical FNPN ) by fusing naphthalene monoimide (NMI) moieties at the bay regions. The optoelectronic characteristics of FPN and FNPN have been investigated. Using PBDB-T as donor material, FPN and FNPN based OSCs provide optimal power conversion efficiency (PCE) of 3.13% and 1.79%, respectively. The higher PCE of FPN based OSCs may be ascribed to the asymmetrical configuration-induced large natural dipole moment and the reinforced intermolecular forces, suggesting that the introduction of asymmetric structure is an effective strategy to improve the photovoltaic performance of PDI based OSCs. Graphical abstract: Image 1